ANALYSIS OF FACTORS THAT CAN AFFECT THE SURPLUS OF THE UNDERWRITING FUND DEFICIT TABARRU ON FULL SHARIA LIFE INSURANCE IN INDONESIA 2014 2019 - Ramidi Ramidi; Jafril Khalil (Proceeding International Seminar of Islamic Studies, 2022)
This study aims to find out what factors can cause a full sharia life insurance company in Indonesia to experience a deficit in the underwriting surplus of tabarru funds in the published annual financial statements, especially in the report of the underwriting surplus (deficit) of tabarru funds. The problem in the field is the occurrence of a deficit in the underwriting surplus of tabarru funds in 3 (three) full sharia life insurance companies in Indonesia. The full sharia life insurance company that experienced a deficit underwriting surplus of tabarru funds in 2014-2019, namely PT. Bumiputera Sharia Life Insurance in 2017 was (9,042.95 billion), and in 2018 it was (5,888.98 billion), PT. Syariah Life Insurance Jasa Mitra Abadi in 2018 amounted to (20.00 million), and in 2019 amounted to (15.492.00 billion), PT. Indonesian Family Sharia Insurance in 2019 amounted to (690.50 billion. The limitation of the problem in this study is what variables can affect the occurrence of an underwriting surplus of tabarru funds. There is one dependent variable, namely the underwriting surplus (deficit) of tabarru funds (Y), while the independent variable has 3 (three) namely the amount of insurance income (X1), total insurance expense (X2) and total investment income (X3). (Sugiyono, 2014 ). The results obtained in this study that the independent variables (amount of insurance income, total insurance expense and total investment income) positively and significantly and together can influence and have a very close relationship to the dependent variable, namely the surplus (deficit) underwriting tabarru funds. .and also other factors. (Priyatno, 2018).